Associations between Housing Factors and Respiratory Symptoms in Two Saskatchewan First Nations Communities - Naiela Anwar; Shelley Kirychuk; Chandima P. Karunanayake; Vivian Ramsden; Brooke Thompson; Eric Russell; Kathleen McMullin; Donna Rennie; Jeremy Seeseequasis; Mark Fenton; Sylvia Abonyi; Punam Pahwa; et al. (International Journal of Environmental Research and Public Health, 2021)
Inadequate housing is commonplace in First Nations in Canada, often leading to environmental impacts on housing such as dampness and mold. First Nations communities suffer from a higher prevalence of respiratory-related health conditions than the general Canadian population. There is limited Canadian literature evaluating the relationship between housing factors and the respiratory health of adults within First Nations communities. This study was undertaken with two Saskatchewan First Nations communities. The study population consisted of 293 individuals within 131 households. The individuals completed questionnaires on their general and respiratory health, and one member of each household completed a household questionnaire. The collection of environmental samples from within the house was undertaken. The respiratory outcomes of interest focused on the individuals with ever wheeze, reported by 77.8% of the individuals, and shortness of breath, reported by 52.6% of the individuals. Body mass index, the nontraditional use of tobacco (i.e., current and ex-smoking), the nontraditional use of tobacco in the house (i.e., smoking in the house), dampness in the house in the last 12 months, and always having a smell of mold in the house were significantly associated with respiratory symptoms. The results reveal that respiratory symptom rates were high in the population and housing factors were significantly associated with respiratory symptoms. Addressing and redressing housing inadequacies in First Nations communities are important in preventing additional burdens to health.